KESENJANGAN MOTIF DAN KEPUASAN MENONTON CHANNEL YOUTUBE “KOK BISA?” DIKALANGAN MAHASISWA ILMU KOMUNIKASI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - M. Taufiq Hidayatullah; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
YouTube Channel "Kok Bisa?" It's one of the most famous educational channels on YouTube with more subscribers than any other education channel. Content given on channel "Kok Bisa?" Draw the attention of audiences to watch the videos. This is in accordance with the assumption of the theory of Use and Gratification of the freedom of the audience in choosing which media can be accepted and satisfy their needs. To measure the satisfaction of the audience by knowing the motive to watch (gratification seeking) and satisfaction after watching (gratification obtained). The purpose of this study is to find information between the motives and satisfaction of the YouTube channel "Kok bisa?" Among students of Communication Studies Faculty of Social and Political Sciences, University of Riau.The method used in this research is quantitative. Data collection techniques in this study using questionnaires. The location of this research is at the Department of Communication Science Faculty of Social and Political Sciences, University of Riau. Sampling using accidental sampling technique with unknown populations formula and get 96 respondents. To know the gap of satisfaction of use, researcher use model of Uses and Gratification which developed by Palmgreen to analyze result.The results of this study show that by looking at the comparison of motive values with student satisfaction in watching YouTube channel "Kok bisa?", The result of calculating the mean value of GS (3.6693) is bigger than the mean value of GO (3.6450). Which means there is a gap of satisfaction because the motive of use is greater than the satisfaction received. This shows that the YouTube channel "Kok can?" Is still not able to satisfy its users.